2014
DOI: 10.1007/s10384-014-0327-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between retinal morphological findings and autoantibody profile in primary Sjögren’s syndrome

Abstract: Compared with controls, eyes with pSS showed thinning of pRNFL and mGCIPL thicknesses. The degree of thinning correlated with increased numbers of the positive autoantibody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…In this current study, although we could not measure the levels of BAFF in the serum of the participants, we postulated that the similarity between the pSS patients and healthy subjects with respect to the thickness of mGCIPL and pRNFL, except in the inferior quadrant, may have been a consequence of the reduced effects of HQ on the serum levels of BAFF in pSS patients (31) . This association may also be supported by the findings of Yang et al who found significant thinning of pRNFL in both the inferior and temporal quadrants as well as the thinning of mGCIPL in nearly all quadrants except the superonasal portion of the macula in pSS patients not under treatment with HQ (21,24) . In the current study, we determined that significant thinning of pRNFL in the inferior quadrant in pSS patients may have arisen from mild macular toxicity of HQ; this finding agreed with that reported by Pa sadhika (32) .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this current study, although we could not measure the levels of BAFF in the serum of the participants, we postulated that the similarity between the pSS patients and healthy subjects with respect to the thickness of mGCIPL and pRNFL, except in the inferior quadrant, may have been a consequence of the reduced effects of HQ on the serum levels of BAFF in pSS patients (31) . This association may also be supported by the findings of Yang et al who found significant thinning of pRNFL in both the inferior and temporal quadrants as well as the thinning of mGCIPL in nearly all quadrants except the superonasal portion of the macula in pSS patients not under treatment with HQ (21,24) . In the current study, we determined that significant thinning of pRNFL in the inferior quadrant in pSS patients may have arisen from mild macular toxicity of HQ; this finding agreed with that reported by Pa sadhika (32) .…”
Section: Discussionsupporting
confidence: 78%
“…It has been reported previously that anti-Ro autoantibodies can play a role in mediating or potentiating vascular injury in the central nervous system (23) . A study by Yang et al indicated that these autoantibodies may also lead to improper apoptotic removal of the retinal ganglion cells (RGCs) by binding to the apoptotic RGCs, resulting in optic nerve damage (24) . Furthermore, in the same study, according to the OCT findings of pSS patients, a correlation was demonstrated between the thinning of pRNFL and mGCIPL and increased numbers of autoantibodies such as anti-Ro and anti-La (23) .…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated pRNFL thickness by SD-OCT and identified reduced thicknesses in the temporal-inferior and the nasal-inferior sectors in SS patients compared with HC and SLE patients. Recent studies in SS patients have shown that the thickness of pRNFL in the inferior quadrants was compromised compared with HC due to dry eye disease or rarely optic neuropathy [44, 45]. This thinning might also be due to HCQ treatment or apoptosis of retinal ganglion cells induced by anti-Ro antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the literature suggest that anti-Ro antibodies could play a role in mediating or potentiating vascular injury in the central nervous system [48]. A study by Yang et al [45] indicated that these antibodies might also lead to improper removal of retinal ganglion cells by binding to apoptotic cells, resulting in optic nerve damage. Moreover, in the same study, a correlation was described between the thinning of pRNFL and increased numbers of anti-Ro and anti-La autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that a failure in the regulation of immunity or aberrant autoimmunity can initiate or aggravate the loss of RGC [ 10 13 ]. Our recent study has revealed that increased positivity for autoantibodies is associated with thinning of the peripapillary retinal nerve fiber layer (pRNFL) or macular ganglion cell–inner plexiform layer (mGCIPL) in patients with pSS [ 14 ]. However, our previous study did not quantify serum autoantibodies and did not evaluate other clinical factors, including histopathologic severity.…”
Section: Introductionmentioning
confidence: 99%